PENGARUH AKUPRESUR PADA TITIK PERICARDIUM 6 TERHADAP FREKUENSI MUNTAH PADA PASIEN DISPEPSIA - Yulisna ' '; Gamya Tri Utami; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purpose of this study was to determine the effect of acupressure at the point of the pericardium 6 to decrease the frequency of vomiting in patients with dyspepsia. This research design was Quasy Experiment with "Non - Equivalent Control Group." Total sample were 30 people, 15 of the respondents were the experimental group and 15 respondents a control group using a sampling technique by simple random sampling with regard inclusion criteria. Measuring instrument used the observation sheet. The analysis used univariate and bivariate analysis with Wilcoxon and Mann Whitney test. The Mann Whitney test showed no significant difference between the frequency of vomiting after acupressure given in the experimental group and the control group was obtained p value = 0.08 (p value> 0.05). While based analysis using the Wilcoxon test showed the influence of a decrease in the frequency of vomiting with p value = 0.004 (p value <0.05). Based on the results of this study, we researchers expected to provide information to develop further research about the other benefits of acupressure at the point pericardium 6 on health with more samples. Keywords: Acupressure, dyspepsia, point pericardium 6, vomiting.